Organ-Preserving Surgery for Penile Carcinoma - Francisco E. Martins; Raul N. Rodrigues; Tomé M. Lopes (Advances in Urology)
Introduction. Penile carcinoma has traditionally been treated by either surgical amputation or radical radiotherapy, both associated with devastating anatomical, functional, and psychological impact on the patient's life. Innovative surgical techniques have focused on penile preservation in well-selected patients to minimize physical disfigurement and consequently maximize quality of life. The objective of this article is to define the current status of these organ-preserving surgical options for penile carcinoma. Materials and Methods. An extensive review of the Pubmed literature was performed to find articles discussing only reconstructive surgery which have contributed significantly to change traditional, frequently mutilating treatments, to develop less disfiguring surgery, and to improve patients' quality of life over the last two decades. Results. Several articles were included in this analysis in which a major contribution to the change in therapy was thought to have occurred and was documented as beneficial. Some articles reported novel techniques of less-mutilating surgery involving different forms of glans reconstruction with the use of flaps or grafts. The issue of safe surgical margins was also addressed. Conclusion. The development of less-disfiguring techniques allowing phallus preservation has reduced the negative impact on functional and cosmetic outcomes of amputation without sacrificing oncological objectives in appropriately selected patients based on stage, grade, and location of the tumour. Until more prospective studies are available and solid evidence is documented, organ preservation should be offered with caution.